Catalog of the vespid wasps of Iran (Hymenoptera, Vespidae) - Ebrahimi, Ebrahim; Carpenter, James M. (Zootaxa, 2008)
Fifty-one genera and 182 species of vespid wasps, belonging to four subfamilies, have been recorded from Iran. A catalog for the region is provided. Locality data for 64 species which were collected or examined during this study are presented. Among them, 10 species represent new records for Iran. An illustrated key to the recorded genera is also presented.